Eco-friendly polymer nanocomposites designed for self-healing applications. (3rd May 2021) - Guadagno, Liberata; Vertuccio, Luigi; Barra, Giuseppina; Naddeo, Carlo; Sorrentino, Andrea; Lavorgna, Marino; Raimondo, Marialuigia; Calabrese, Elisa
Abstract: Fully biodegradable self-healing nanocomposites were prepared by mixing carbon nanotubes (CNTs)-based carboxyl methyl cellulose (CMC), produced by chemical modification of cellulose, with a commercial biodegradable highly amorphous vinyl alcohol polymer (HAVOH) containing murexide salt. Damaged specimens were allowed to cure by simply touching the cutting sections in a controlled temperature and humidity environment (30 °C and 80%) for a period of 48 h. The healing efficiency of the samples, evaluated by the recovery of the "Storage Modulus" determined by dynamic-mechanical analysis (DMA) of healed samples, manifests a temperature-dependence behaviour. For temperatures above 50 °C, an almost complete recovery (100%) was observed for the sample of HAVOH containing a solubilized murexide salt. The presence of CNTs-based CMC imparts improved mechanical properties. Maximum values for healing efficiency were observed between 30 and 80 °C. Graphical abstract: Image 1 Highlights: Green self-healing nanocomposites have been successfully designed. They have been prepared by employing natural resources such as modified cellulose. The modified cellulose confers to the samples a better mechanical performance. Maximum values of healing efficiency are recorded between 30 and 80 °C. The formulated samples reduce environmental pollution due to plastic materials.